P19 Relationship between cardiac autonomic function and novel echocardiography indices of left ventricular function. (21st September 2022) - Rahman, Mushidur; Russell, Sophie L; Banerjee, Prithwish; Maddock, Helen; Okwose, Nduka C; Jakovljevic, Djordje G
Abstract : Objective: Heart rate variability (HRV) is a measure of cardiac autonomic function. This study evaluated the relationship between HRV and echocardiography derived measures of cardiac function. Methods: Thirty healthy participants (age 33±10 years) underwent five-minute HRV measurement and echocardiography at rest. HRV variables included: R-R average, standard deviation of normal RR intervals (SDNN), root mean square of successive RR interval difference (RMSSD), low-frequency power (LF), high-frequency power (HF), low-frequency in normalised units (LFnorm) and high-frequency normalised units (HFnorm). Left ventricular ejection fraction (LVEF), left ventricular global longitudinal strain (LV-GLS), left atrial strain: reservoir (LAres), conduit (LAcon) and contraction (LACT), stroke volume (SV) and cardiac output (CO) were evaluated via speckle tracking and pulse-wave Doppler. Results: The mean values of R-R average (991±176), SDNN (50.9±21.5 ms), RMSSD (46.8±29.4 ms), LF (727±606 ms2), HF (415±35 ms2), LFnorm (56±19.4) and HFnorm (36.5±18.8), LV-GLS (19.2±1.37%), LV-EF (59.9±2.78%), RV-GLS (21.7±2.69%), LAres (36.8±6.99%), LAcon (26.2±6.95%), LACT (12.3±3.56%), SV (71.5±16.2 ml) and CO (4.58±1.48l/min). RMSSD had a positive relationship with LVEF (r=0.39, p=0.03) and stroke volume (r=0.40, p=0.03); SDNN with stroke volume (r=0.39, p=0.04) and HF with cardiac output (r=0.50, p=0.01) and LV-GLS (r=-0.47, p=0.01). However, measures of HRV were not significantly correlated with RV-GLS or measures of left atrial function (p>0.05). Conclusion: Heart rate variability may be considered as an indicator of left ventricular contractile and haemodynamic function. HRV can be considered as an indicator of left ventricular function and used as a simple tool to monitor improvement or deterioration in cardiac function.